Soviet military operation in Afghanistan and regional and international factors (1979) (1) - مستەفا, ئارام علی; ساڵح, گۆران ئیبراهیم (Sulaimani Journal for Humanities, 2019)
After Islamic Revolution of Iran, The Soviet invasion of the Afghanistan in late December 1979 has had Impact on Regional and International Relations, Also The Soviet Military Poses on Afghanistan, was the source of increased hostilities of Cold War between the United States and the Soviet Union in the 1980s, Because the belief among US foreign policy-makers that the Soviet Union was finally embarking on their longtime mission of advancing upon the oil of the Persian Gulf, the warm water ports of the Arabian Sea, and Controlling the South Asia, was finally supported-a propaganda defeat for the Soviet Union. But Soviet Union Declared That Military Poses in order to help the Democratic Republic of Afghanistan, a communist state that was dependent on the Soviet Union. The study consists of One parts, and Three Branches, With the List of Sources and Conclusions, In this Study We Try to Focused on the Soviet Military Invasion of Afghanistan and Analyses of all Internal, Regional and International Factors. The study has depended on many Sources and documents.